Educational interventions for patients with heart failure: a systematic review of randomized controlled trials - Kroustalli, Elpida; Papadopoulos, Constantinos H.; Vasileiadis, Ioannis; Karatzanos, Eleftherios; Nanas, Serafim (Health & Research Journal, 2019)
Background: Patient education is an important intervention for the management of heart failure; however, in practice patient education varies considerably. The purpose is to systematically review educational interventions that have been implemented for heart failure patients and assess their effectiveness. Method and Material: Randomized controlled trials from 2008 to 2018 in MEDLINE were reviewed using the following search terms: nursing teaching, education, intervention, patients with heart failure, hospital. From the Randomized controlled trials 26 abstracts were reviewed. Results: A total of 2484 patients were included in the 19 studies that met the inclusion criteria. Commonly, the initial educational intervention was a one-on-one didactic session conducted by nurses supplemented by written materials and multimedia approaches. One study referred to a theoretical model as a framework for their educational intervention. Studies used a variety of outcome measures to evaluate their effectiveness. Of the studies reviewed, 17 demonstrated a significant effect from their intervention in at least one of their outcome measures. Conclusions: Despite improvements in knowledge, we have variable results in outcomes and this is very likely related to the heterogeneity of the studies included in this review. It was difficult to establish the most effective educational strategy as the educational interventions varied considerably in delivery methods and duration as well as the outcome measures that were used for the evaluation. A patient-centered multidisciplinary approach based on educational theory and evaluated appropriately may assist to develop an evidence base for patient education.